Philosophy as the Foundation for the Development of Modern Pedagogical Science - Rangkuti, Alpan Noor Habib; Sauri, Sofyan (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study examines the relevance of philosophy in the development of modern pedagogical science, focusing on the application of Islamic philosophy in education during the era of globalization. The background of this research lies in the increasingly complex challenges of education, such as the advancement of digital technology, cultural diversity, and the demands for competency-based learning. This study aims to explore how philosophy, particularly Islamic philosophy, can provide a strong philosophical foundation for developing educational theories and practices relevant to the needs of modern society. The method employed is a qualitative approach with a literature review. Data were collected by analysing literature related to educational philosophy, epistemology, ontology, and axiology. The findings reveal that philosophy, especially Islamic philosophy, provides a robust theoretical basis for developing holistic education that integrates intellectual, moral, and spiritual dimensions. Applying Islamic philosophical values can cultivate academically intelligent, morally upright individuals capable of addressing global challenges. This study concludes that Islamic philosophy is highly relevant in addressing modern educational challenges by integrating academic, moral, and spiritual aspects into a comprehensive educational curriculum.